Three Body Mass Index Classification Comparison In Predicting Hypertension Among Middle-Aged Indonesians - Tri Sutanti Puji Hartati; Emyr Reisha Isaura (Universitas Airlangga, 2023)
Cardiovascular disease is one of the severe causes of death in low-middle-income countries. Being overweight and obese relates to a higher risk of hypertension, which further increases the risk of CVD. Therefore, determining body mass index (BMI) cut-off points is essential to provide a new scale for early and accurate screening. This study aimed to compare three classifications of BMI defined by WHO, Indonesia, and Asian criteria in predicting hypertension in middle-aged Indonesians. We used the 2014 Indonesian Family Life Survey data and included a total sample of 9737 respondents aged 40-60-year-old. We compared values (specificity, sensitivity, negative and positive predictive value, false-positive rate, negative and positive likelihood ratio, Youden index, and prevalence) of three BMI criteria (WHO, Indonesian, and Asian) between groups (Group 1: normal BMI vs overweight + obese BMI; group 2: normal + overweight BMI vs obese BMI) to determine the cut-off points of BMI related to hypertension. The hypertension prevalence was significantly higher in women (48.3%) than in men (42.0%). Respondents’ BMI was positively associated with hypertension. The Asian BMI classification showed better sensitivity, specificity, PPV, NPV, FPR, LR+, LR-, and Youden index in group 1 than in group 2. Thus, this study proposed a fitted BMI cut-off point for overweight was ≥23 kg/m2 and for obesity was ≥25 kg/m2 as the early screening of overweight and obesity related to hypertension among the middle-aged population in Indonesia.